¿Es la genealogía foucaultiana una nueva forma de historia? - Hulak, Florence (Conceptos Históricos, 2017)
This paper shows that at the end of the 1976 lecture –Society Must Be Defended– Michel Foucault concluded that genealogy does not constitute a new way of history. The invention of genealogy had provided the specific historical perspective of which the archeology lacked: the analysis of force-relations. However, genealogy only can construct an actual history if it is able to explain the formation of society. That was the purpose of that lecture. Nevertheless, in trying to find, one more time, war beneath society, Foucault rather found the society beneath force-relations. This observation led him to quit thinking genealogy as a historical discourse capable of rivalizing with the one of the social sciences.